Colour Change and Surface Gloss of Unpolished Infiltrated Bovine Enamel Submitted to Toothbrushing, pH Cycling and Artificial Ageing - Souza Barboza, Ana Carolina [UNESP]; Fraga Briso, Andre Luiz [UNESP]; Moda, Mariana Dias [UNESP]; Gallinari, Marjorie De Oliveira [UNESP]; Bresciani, Eduardo [UNESP]; Dos Santos, Paulo Henrique [UNESP]; Fagundes, Ticiane Cestari [UNESP] (Premchand Shantidevi Research Foundation, 2019)
Introduction: The first clinical sign of a caries lesion which represents mineral loss from the enamel subsurface is white spot lesion. Thus, the use of a resin infiltrant has been cited as a promising treatment, once the resin infiltrant promotes an obstructive effect, hindering the progression of lesions by preventing the diffusion pathways for cariogenic acids. Aim: To evaluate the colour change and surface gloss of white spot lesions after application of unpolished resin infiltrant submitted to toothbrushing, pH cycling and artificial ageing. Materials and Methods: The present in-vitro study was conducted from June 2014 to September 2014. This study was related to the Aracatuba School of Dentistry, Sao Paulo State University (UNESP), Aragatuba, Sao Paulo, Brazil. Fifty Bovine enamel discs were divided into five groups (n=10) white spot lesion (W-control), infiltrated white spot lesion (IW), infiltrated white spot lesion submitted to toothbrushing (IWb), infiltrated white spot lesion submitted to pH cycling (IWc), and infiltrated white spot lesion submitted to artificial ageing (IWa). After the challenges, the specimens were evaluated for colour change using L*a*b*system (CIELAB), and surface gloss analysis was performed using a gloss meter. The data were submitted to oneway ANOVA and Tukey's test for multiple comparisons (p<0.05). Kruskal-Wallis and Dunn's tests were used for the final surface gloss and Delta a. Results: When considering the Delta E. all groups were similar (p>0.05). All groups receiving resin infiltrant (IW, IWb, IWc, IWa) presented lower surface gloss when compared to W group (p<0.05). Conclusion: No colour change was observed when the samples were subjected to different challenges. Unpolished resin infiltrant appeared to reduce the surface gloss of enamel independently if it is challenged. The differences in the mean colour and gloss changes were similar for all challenges.
Keywords: Cariogenic acids; Dental caries; Dental enamel; White spot lesion